2015
DOI: 10.1037/xhp0000050
|View full text |Cite
|
Sign up to set email alerts
|

The selection and usage of information for perceiving and remembering intended and unintended object properties.

Abstract: The current study was designed to investigate the linkage between intention, attention, and information selection and detection. Two experiments determined whether the intention to perceive maximum overhead reaching height with the use of handheld rods with different rotational inertia resulted in the ability to remember the rods' heaviness after they were removed from view. Participants were partially successful at distinguishing the heaviness of rods but only when visual information was restricted and reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous research has demonstrated that sport-specific personal and interpersonal affordances can be perceived in the context of both individual and team sports (Passos et al, 2012; Peker, Böge, et al, 2020; Peker, Erkmen, et al, 2020; Zheng et al, 2022). Moreover, previous research has shown that perception of higher-order affordances is not a simple additive combination of either properties of the animal or environment or lower-order affordances (Thomas et al, 2018; see also Thomas & Riley, 2014, 2015; Wagman & Stoffregen, 2020). Our results both build on and extend these findings by showing that (a) sport-specific combinations of personal and interpersonal constraints yield higher-order affordances and (b) that awareness of such higher-order affordances is not a simple additive combination of the constituent lower-order personal and interpersonal affordances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that sport-specific personal and interpersonal affordances can be perceived in the context of both individual and team sports (Passos et al, 2012; Peker, Böge, et al, 2020; Peker, Erkmen, et al, 2020; Zheng et al, 2022). Moreover, previous research has shown that perception of higher-order affordances is not a simple additive combination of either properties of the animal or environment or lower-order affordances (Thomas et al, 2018; see also Thomas & Riley, 2014, 2015; Wagman & Stoffregen, 2020). Our results both build on and extend these findings by showing that (a) sport-specific combinations of personal and interpersonal constraints yield higher-order affordances and (b) that awareness of such higher-order affordances is not a simple additive combination of the constituent lower-order personal and interpersonal affordances.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wagman and Stoffregen (2020) showed that perceived maximum reaching heights both with and without a tool was not a simple additive combination of the perceived animal and environment properties that comprised that affordance (perceived shoulder height, perceived arm length, tool length). Similarly, perception of maximum jump-and-reach height is not a simple additive combination of perceived maximum stand-and-reach height and perceived maximum jump height (Thomas et al, 2018; see also Thomas & Riley, 2014, 2015; Wagman, Thomas, & McBride, 2019). In the present study, we investigated these issues in the context of higher-order affordances for kicking in soccer.…”
Section: Affordances: Lower- and Higher-ordermentioning
confidence: 99%
See 1 more Smart Citation